Meningkatkan Kemampuan Teknik Dasar Dribbling Melalui Penggunaan Video Feedback (VFB) Dalam Pembelajaran Futsal - Ribut Wahidi; Iif Firmana; Oman Hadiana; Nurlan Kusmaedi; Amung Ma’mun; Boyke Mulyana; Bangbang Syamsudar (Universitas Pendidikan Indonesia, 2021)
This study aimed to help improve the basic futsal techniques through video feedback (VFB) in futsal learning. The research method used was the pre-experimental method with a one-group pretest-posttest design. The research was conducted in a university, specifically in the Physical Education Health and Recreation Study Program, involving 34 students as the samples. The samples were then received feedback via VFB. The instrument to measure the basic technique was the Dribbling test. The results showed a significant improvement in the basic dribbling technique after using VFB in futsal learning. Futsal learning activity using VFB is one of the strategies in Physical Education learning to optimize the classroom environment, improve basic techniques, increase competence, improve playing skills, and explore physical motor activities. It concludes that Video Feedback significantly improves student skills. The use of audio-visual media (video) also has high effectiveness in the training or learning process. It is crucial for students learning to carry out the exercise material effectively in the learning process. Future research is expected to use VFB to determine the student's cognitive ability and futsal playing skills.